Promotility Action of the Probiotic Bifidobacterium lactis HN019 Extract Compared with Prucalopride in Isolated Rat Large Intestine - Dalziel, Julie E.; Anderson, Rachel C.; Peters, Jason S.; Lynch, Amy T.; Spencer, Nick J.; Dekker, James; Roy, Nicole C. (Frontiers in Neuroscience, 2017)
Attention is increasingly being focussed on probiotics as potential agents to restore or improve gastrointestinal (GI) transit. Determining mechanism of action would support robust health claims. The probiotic bacterium Bifidobacterium lactis HN019 reduces transit time, but its mechanisms of action and effects on motility patterns are poorly understood. The aim of this study was to investigate changes in GI motility induced by an extract of HN019 on distinct patterns of colonic motility in isolated rat large intestine, compared with a known promotility modulator, prucalopride. The large intestines from male Sprague Dawley rats (3-6 months) were perfused with Kreb’s buffer at 37 °C in an oxygenated tissue bath. Isometric force transducers recorded changes in circular muscle activity at four independent locations assessing contractile propagation between the proximal colon and the rectum. HN019 extract was perfused through the tissue bath and differences in tension and frequency quantified relative to pre-treatment controls. Prucalopride (1 µM) increased the frequency of propagating contractions (by 75 ± 26 %) in the majority of preparations studied (10/12), concurrently decreasing the frequency of non-propagating contractions (by 50 ± 11 %). HN019 extract had no effect on contractile activity during exposure (n=8). However, following wash out, contraction amplitude of propagating contractions increased (by 55 ± 18 %) in the distal colon, while the frequency of non-propagating proximal contractions decreased by 57 ± 7 %. The prokinetic action of prucalopride increased the frequency of synchronous contractions along the length of colon, likely explaining increased colonic rate of transit in vivo. HN019 extract modified motility patterns in a different manner by promoting propagating contractile amplitude and inhibiting non-propagations, also demonstrating prokinetic activity consistent with the reduction of constipation by B. lactis HN019 in humans.